Evaluation of EAP Short Essay Writing Textbooks: An Analysis of Content Quality in Developing Academic Writing Skills - Arzaqi, Dimas; Diah Puji Siliwangi; Abdul Syahid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
A This study evaluates EAP (English for Academic Purposes) short essay writing textbooks, focusing on the quality of content and its role in developing students' academic writing skills. The analysis examines the alignment of textbook materials with academic writing standards, including structure, coherence, and argumentation. Through a systematic review of selected textbooks, the study identifies strengths and weaknesses in content presentation, instructional support, and relevance to learners' needs. The findings reveal critical insights into how these resources can enhance writing proficiency, offering recommendations for educators and curriculum developers. Ultimately, this research aims to contribute to the improvement of EAP instruction by providing a framework for assessing the effectiveness of educational materials in fostering essential writing competencies.